Al-Tahlil Al-Taqabuliy baina Al-Lughah Al-Indunisiyyah wa Al-Lughah Al-‘Arabiyyah ‘ala Mustawa ‘Alamat Al-Tarqim fi Al-Kitabah - Mudlofir, Ali; Alwachidah, Khoirun Nisa; Muflihah, Muflihah; Hanifah, Umi (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Scholars agree that similarities are one of the reasons for the ease with which students learn a second language, and differences are the reason for difficulties in learning it. This study discusses the contrastive analysis between Indonesian and Arabic regarding the chapter on punctuation marks and their benefits in learning writing skills for students of class X MAN 1 Pasuruan. The formulation of the problem in this study are: 1- What are the similarities and differences between Indonesian and Arabic regarding the punctuation chapter? 2- What are the benefits of the results of the contrastive analysis between Indonesian and Arabic regarding the chapter on punctuation marks and their benefits in learning writing skills for class X students of MAN 1 Pasuruan? The research method used by the researcher is descriptive qualitative method. Collecting data using observation method, interview method, test method, and documentation method. The research sample was all students of class X MIA II MAN 1 Pasuruan, totaling 34 students. The research results can be summarized as follows: There are similarities and differences in types and functions between Indonesian and Arabic punctuation marks, and there are benefits from applying the results of this analysis, it was found that the percentage of punctuation scores from the post-test reached 75.8%, and This result is greater than the pre-test result which was 58.9%. Ø£ÙƒØ¯ Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø£Ù† Ø§Ù„ØªØ´Ø§Ø¨Ù‡ Ø³Ø¨Ø¨Ø§ Ù„Ø³Ù‡ÙˆÙ„Ø© Ø§Ù„Ø¯Ø§Ø±Ø³ÙŠÙ† ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø«Ø§Ù†ÙŠØ© Ø§Ù„Ø§Ø®ØªÙ„Ø§Ù Ø³Ø¨Ø¨Ø§ Ù„ÙˆØ¬ÙˆØ¯ Ø§Ù„ØµØ¹ÙˆØ¨Ø§Øª ÙÙŠ ØªØ¹Ù„Ù…Ù‡Ø§ØŒ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙŠØ¨ØØ« Ø¹Ù† Ø§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ØªÙ‚Ø§Ø¨Ù„ÙŠ Ø¨ÙŠÙ† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ Ù…Ø³ØªÙˆÙ‰ Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªØ±Ù‚ÙŠÙ…Â ÙˆØ§Ù„Ø§Ø³ØªÙØ§Ø¯Ø© Ù…Ù†Ù‡ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù†. ÙØªØ¨ØØ« Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¨Ù‚Ø¶Ø§ÙŠØ§ Ø§Ù„Ø¨ØØ« : 1- Ù…Ø§ Ø£ÙˆØ¬Ù‡ Ø§Ù„ØªØ´Ø§Ø¨Ù‡ ÙˆØ§Ù„Ø§Ø®ØªÙ„Ø§Ù Ø¨ÙŠÙ† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ Ù…Ø³ØªÙˆÙ‰ Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªØ±Ù‚ÙŠÙ…ØŸ 2- ÙƒÙŠÙ Ø§Ù„Ø§Ø³ØªÙØ§Ø¯Ø© Ù…Ù† Ù†ØªØ§Ø¦Ø¬ Ø§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ØªÙ‚Ø§Ø¨Ù„ÙŠ Ø¨ÙŠÙ† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ Ù…Ø³ØªÙˆÙ‰ Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªØ±Ù‚ÙŠÙ… Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù†ØŸ. ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¨ØØ« Ø§Ù„ØªÙŠ Ø§Ø³ØªØ®Ø¯Ù…ØªÙ‡Ø§ Ø§Ù„Ø¨Ø§ØØ«Ø© Ù‡ÙŠ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ÙƒÙŠÙÙŠØ© Ø§Ù„ÙˆØµÙÙŠØ©. ÙˆÙ„Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ø³ØªØ®Ø¯Ù…Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ù„Ø§ØØ¸Ø©ØŒ Ùˆ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø©ØŒ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø±ØŒ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„ÙˆØ«Ø§Ø¦Ù‚ØŒ Ø£Ù…Ø§ Ø¹ÙŠÙ†Ø© Ø§Ù„Ø¨ØØ« ÙÙ‡ÙŠ Ø¬Ù…ÙŠØ¹ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¹Ø§Ø´Ø± Ù„Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„Ø·Ø¨ÙŠØ¹Ø© Ø§Ù„Ø«Ø§Ù†ÙŠ Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù† ÙˆÙ‡Ù… Û³Ù¤ Ø·Ø§Ù„Ø¨Ø§. ÙˆØ£Ù…Ø§ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« ÙÙŠÙ…ÙƒÙ† Ø£Ù† ØªØªÙ„Ø®Øµ: Ù‡Ù†Ø§Ùƒ Ø£ÙˆØ¬Ù‡ Ø§Ù„ØªØ´Ø§Ø¨Ù‡ ÙˆØ§Ù„Ø§Ø®ØªÙ„Ø§Ù Ø§Ù„Ù†ÙˆØ¹ÙŠ ÙˆØ§Ù„ÙˆØ¸ÙŠÙÙŠ Ø¨ÙŠÙ† Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªØ±Ù‚ÙŠÙ… Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© ÙˆØ§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆÙˆØ¬Ø¯Øª Ø§Ù„Ø§Ø³ØªÙØ§Ø¯Ø© Ù…Ù† Ù‡Ø°Ù‡ Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠØ©ØŒÂ Ø£Ù† Ù…Ø¹Ø¯Ù„ Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø§Ù„Ù…Ø§Ø¦ÙˆÙŠØ© Ø¹Ù† Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªØ±Ù‚ÙŠÙ… Ù…Ù† Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ Ø¨Ù„Øº 75.8%ØŒ ÙˆÙ‡Ø°Ù‡ Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø£ÙƒØ¨Ø± Ù…Ù† Ù†ØªÙŠØ¬Ø© Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠ Ø§Ù„Ø°ÙŠ Ø¨Ù„Øº 58.9%.